Fundamentals compaction of bi-layered tablets - Abu Bakar, Nurhamimah; Mohamad, N. S.; Anuar, Mohd Shamsul; Mohd Tahir, Suraya (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Bi-layered tablets are produced by having two pharmaceutical powders, confined within a die, compacted under certain amount of load consecutively one after another. In this study the bi-layered tablets are made of microcrystalline cellulose (MCC), which is commonly used as a binder in pharmaceutical tablets due to its good compaction properties, and lactose which has a poor compactibility in contract to MCC. The objective of this study is to investigate the characteristics and mechanical strength of bi-layered tablets after the ejection process. With variations of processing parameters and raw material compositions the tablets are formed by using the Instron Universal Testing Machine. The compaction load for the bottom layer is kept constant at 3kN (22.6MPa) while the top layer compaction load ranges from 3kN (22.6MPa) to 24kN (180.83MPa). From the compaction process the plastic and elastic energy curves of the powders, the ejection curves as well as the diametrical relaxation of the tablets are observed. Indirect tensile strength test was conducted 24 hours after the ejection process. The plastic and elastic energy for both powders increases with increasing compaction load. The tensile strength of the tablets increases as the compaction loads increases for the top layer. The tablets with microcrystalline cellulose as the top layer have a higher tensile strength in contrast to tablets with lactose as the top layer.